Is long-period time charters still a viable option in today's market conditions? - Ng, Jin Yuan (Nanyang Technological University, 2018)
Intense volatility of the freight market has beleaguered the shipping industry for many years in what seems like a rollercoaster ride with many ups and downs and such volatility represents a substantial financial risk for shipowners. Thus, it is important for shipowners to engage in strategic fleet planning to optimize their selections of long-term and spot contracts among their fleet to minimize their exposure to the volatility of the freight market and achieve profit. Current researches on the optimization of fleet planning mainly focus on Liner trade; therefore, this report aim to bridge the gap by studying the dry bulk market, with an emphasis on the Handysize and Handymax sector. Four significant factors influencing the freight market, namely Commodities’ Demand, New orders of Handysize and Handymax vessels, Demolition rate of Handysize and Handymax vessels and the Handysize and Handymax fleet size will be examined and analyzed. The future spot freight rate will be projected to determine the viability of long period time charter in today’s market condition. In this study, two forecasting models, Triple Exponential Smoothing and Linear Regression, were used to project the trend of the above factors and the relevant Baltic Index to attain the projected trend of the time charter hire. The result of this study suggests that the long period time charter contracts is not profitable for Handysize vessel due to the continued bearish outlook of the market. However, Handymax market remains bullish and time charter contracts remain a viable option in today’s market condition.